A methods engineering study on United Parens Manufacturing Corporation - Agno, Kristine Lufel; Jalao, Eugene Rex.; Patawaran, Ma. Rizza (Diliman, Quezon City College of Engineering, 2005)
United Parens Manufacturing Corporation (UPMC) is a small manufacturing firm located at San Pedro Coliseum Compound, San Pedro, Laguna. It is situated near Pacita Complex. It caters to the needs of metal products of car and bus assemblers, construction companies, electronics manufacturers, truck special body builders, bus companies, assembly plants and semiconductor plants. Some of its customers are Asian Carmakers Corporation (maker of KIA vehicles), Columbian Manufacturing Corporation (assembler of buses), Pilipinas Daewoo, and COSMOS Bottling Corporation. During the group's plant visits, the following problems were identified : interruption of work to fix a failure in the machine, interruption of work to give way to other workers, inefficiency of methods that leads to frequent overtime among workers, inconsistencies in the method of performing some of its operations, poor plant layout and inadequate lighting. The group came up with recommendations to address these problems. A new plant layout was designed to address the problems due to the layout. Also, the group recommended a substitute process that takes a lesser time compared to the present process (i.e. drilling was suggested to be replaced with punching), without sacrificing the quality of the product. Other recommendations like supervision of workers, installation of a Bundy clock system and installation of additional lighting were also suggested to further improve the general condition of the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: United Parens Manufacturing Corporation; Metal trade; Systems analysis